The socioeconomics support on indigenous Community in Malaysia - Muhammad Fuad Abdullah; Badli Esham Ahmad; Mohd Iqbal Mohd Noor; Lindah Roziani Jamru; Mohamad Pirdaus Yusoh (University of Malaya, 2023)
The Malaysian community has been impacted by the government development programs that were put in place. The effects of development that have been changing the socioeconomic atmosphere of populations are not limited to mainstream races but also to vulnerable communities like Orang Asli. Many development programmes have been implemented to uplift the well-being of Orang Asli since before Independence Day in 1957. Thus, this study aims to investigate the efficiency of socioeconomic support programmes in the Orang Asli community to bring them out of multidimensional poverty. This study was done on the head of household (HoH) of the Orang Asli community living near the National Park in Pahang. SEM Amos analysis was used to validate all the hypotheses about dependent variables: education, health, the standard of living and wealth. Only the indicators in the health dimension have negative values. This indicates that both indicators, child mortality rate and nutrition, are good in all three Orang Asli settlements. Besides that, logistic regression shows that only the indicators in the health dimension have negative values, indicating that both indicators, child mortality rate and child nutrition, are good in all three Orang Asli settlements. Therefore, any responsible bodies need to emphasise these particular deprivation matters to uplift the well-being status of the Orang Asli. In addition, serious involvement in the tourism sector is the better option to bring this community out of deprivation, as they live in an attractive and tourism-driven area, the National Park.